Pengaruh struktur kepemilikan institutional, struktur kepemilikan manajerial, struktur kepemilikan publik, debt covenant dan growth opportunities Terhadap konservatisme akuntansi - Sari, Dewi Nadia; L, Al-azhar; ', Yusralaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to prove The Influence of Institutional Ownership Structure, Managerial Ownership Structure, Public Ownership Structure, Debt covenant and Growth Opportunities Towards Accounting Conservatism. Population will be the object of this research is all manufacturing companies that have been recorded and published financial statements in Indonesian Stock Exchange from 2010-2012. Data analysis method used is multiple linear regression model (multiple regression).Based on the results of the discussion over the whole hypothesis testing are: 1) Institutional Ownership Structure variable (SKI) had no effect on the variable Conservatism, 2) Managerial Ownership Structure variables (SKM) had significant negative effect on the variable Conservatism. 3) Public Ownership Structure (SKP) had no significant positive effect on the variable Conservatism, and 4) Debt to Covenant variable had significant positive effect on conservatism variables, and 5) Growth Opportunities variable had no significant positive effect on the variable Conservatism.Keywords : Institutional Ownership Structure, Managerial Ownership Structure, Public Ownership Structure, Debt covenant Growth Opportunities, Accounting Conservatism